In vitro modulatory effect of nanoencapsulated tocotrienol-rich fraction, ascorbyl tetraisopalmitate, and carotenes on atopic dermatitis-like model of human epidermal keratinocytes - Gan, Yee-Lin; Tan, Chin-Ping; Cheah, Yoke-Kqueen; Ariffina, Hidayah; Wasoh, Helmi; Lai, Oi-Ming (Malaysian Society for Molecular Biology and Biotechnology, 2024)
The aim of the study was to investigate the regulatory effects of mixed antioxidants, including tocotrienol-rich fraction, ascorbyl tetraisopalmitate, and carotenes, on inflammatory response and epidermal integrity of normal human epidermal keratinocytes (NHEK) stimulated with cytokines to mimic atopic dermatitis (AD). Nano encapsulated mixed antioxidants (NMA) were prepared by encapsulating tocotrienol-rich fraction, ascorbyl tetraisopalmitate and carotenes into nanoemulsion. The interleukin (IL)-4 (50 ng/mL), interferon (IFN)-γ (50 ng/mL), and tumor necrosis factor (TNF)-α (20 ng/mL) individually stimulated NHEK cells were treated with NMA (2.1-2100 ng/mL). Then, cytokines, chemokines and structural proteins expressions were determined. Cell monolayer integrity was assessed using dispase-based keratinocyte dissociation and wound-healing assays.The key findings of the study showed that NMA treatment (2100 ng/mL) resulted in a complete abolishment of upmodulation thymic stromal lymphopoietin (TSLP) expression induced by IL-4, IFN-γ, and TNF-α. Upregulated expression of thymus and activation regulated chemokine (TARC) following IL-4 stimulation was attenuated by NMA (2.1-2100 ng/mL). The increment of interferon gamma-induced protein 10 (IP-10) and monocyte chemoattractant protein-1 (MCP-1) expressions resulting from IL-4, IFN-γ, and TNF-α stimulations was significantly suppressed by NMA treatment. The downregulated filaggrin expression provoked by IL-4 and TNF-α stimulations was abrogated with NMA treatment (2.1-2100 ng/mL). Treatment with NMA significantly improved the production of cornified envelope proteins, decreased the dissociation scores and accelerated wound healing of IL-4, IFN-γ, and TNF-α stimulated NHEK.